Genome-wide identification and expression analysis of the MORF gene family in celery reveals their potential role in chloroplast development - Pei-Zhuo Liu; Ya-Hui Wang; Yue-Hua Sun; Yong-Ju Wei; Xu Sun; Meng-Yao Li; Guo-Fei Tan; Ai-Sheng Xiong (Journal of Genetic Engineering and Biotechnology)
Chlorophyll is an important nutrient in celery and one of the main indexes of quality evaluation. RNA editing in chloroplasts is an important factor affecting chloroplast development and chlorophyll biosynthesis. Multisite organelle RNA editing factor (MORF) protein is a necessary regulator of chloroplast RNA editing. In this study, a total of 8 MORF genes in celery were identified, which were named AgMORF1a, AgMORF1b, AgMORF2a, AgMORF2b, AgMORF3, AgMORF7, AgMORF8 and AgMORF9 according to their subfamily classification. The physicochemical property, conserved motifs, cis-acting elements and protein interaction were predicted according to the sequences. The phylogenetic relationships and evolutionary selective pressure between MORF genes in celery and other Apiaceae plants were further analyzed. The results showed that AgMORF1b, AgMORF2a, AgMORF2b and AgMORF9 were predicted to be localized in chloroplasts. The evolution of MORF genes in 4 Apiaceae plants including celery, carrot, coriander and water dropwort was influenced by purify selection. Transcriptome data showed that the transcriptional levels of AgMORF2a, AgMORF2b, AgMORF8 and AgMORF9 were relatively higher among all MORF genes in petioles of celery, indicating their major role. RT-qPCR data showed that the expression levels of the above 4 genes were significantly higher in petioles of green celery than those of white celery. This study provided a basis for analyzing the effects of MORF proteins on chloroplast development of celery with different chlorophyll accumulation.